The Characters and Conflicts in Marvel Studios “Doctor Strange” Movie - Ayu Mitha Hapsari, Ni Putu (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p30, 2018)
The title of this paper is The Characters and Conflicts in Marvel Studios “Doctor Strange” Movie. This study focus es on categorization and function of the characters in the movie and conflicts in the main character (external and internal conflicts). The data of this study were taken from a movie entitled Doctor Strange. The data were collected through documentation method. In analyzing the data, the study used qualitative method. The categorization and function were analyzed based on the theory proposed by Wellek and Warren (1955:227) , supported by the theory of literature proposed by Kathleen Morner (1991:31). The conflict was analyzed based on the theory of literature proposed by Kenney (1966:5). The findings show that the categorization and function of the characters in the movie are as follows: Stephen Strange (dynamic protagonist character), Kaecilius (static antagonist character). Secondary characters are The Ancient One (static protagonist character), Mordo (static protagonist character) and Christine (dynamic protagonist character). The s upporting character is Wong (static protagonist character). Then there are two types of conflict s found in this movie, internal and external conflict s .